2011 23rd Euromicro Conference on Real-Time Systems 2011
DOI: 10.1109/ecrts.2011.23
|View full text |Cite
|
Sign up to set email alerts
|

On the Tractability of Digraph-Based Task Models

Abstract: Abstract-In formal analysis of real-time systems, a major concern is the analysis efficiency. As the expressiveness of models grows, so grows the complexity of their analysis. A recently proposed model, the digraph real-time task model (DRT), offers high expressiveness well beyond traditional periodic task models. Still, the associated feasibility problem on preemptive uniprocessors remains tractable. It is an open question to what extent the expressiveness of the model can be further increased before the feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Schedulability analysis has been developed for a variety of different task models, including: periodic tasks [19], sporadic tasks [22], multi-frame tasks [34], [23], generalised multiframe (GMF) tasks [5], non-cyclic GMF tasks [24], recurring real-time tasks [6], non-cyclic recurring real-time tasks [7], and the digraph task model [28], extended with constraints in [29]. Currently, the most general is the digraph task model which describes each task via a directed graph.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Schedulability analysis has been developed for a variety of different task models, including: periodic tasks [19], sporadic tasks [22], multi-frame tasks [34], [23], generalised multiframe (GMF) tasks [5], non-cyclic GMF tasks [24], recurring real-time tasks [6], non-cyclic recurring real-time tasks [7], and the digraph task model [28], extended with constraints in [29]. Currently, the most general is the digraph task model which describes each task via a directed graph.…”
Section: A Related Workmentioning
confidence: 99%
“…An edge is labelled with the minimum time between activations of the jobs it connects. Constraints are added to this in [29] to specify a minimum time between nodes.…”
Section: A Related Workmentioning
confidence: 99%
“…A natural representation of these complex structures is a task graph. Over years, more and more expressive graph-based task models are proposed to precisely describe complex embedded real-time systems [11], [5], [2], [3], [4], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that for EDF, schedulability of DRT task sets can be checked in pseudo-polynomial time [2]. Even for an extension of DRT tasks with global timing constraints, this problem has been shown to be tractable [6].…”
Section: B Schedulabilitymentioning
confidence: 99%
“…It models each task with a directed graph in which vertices represent job releases and edges represent branching structures and inter-release delays. A recent extension to this model with global timing constraints [6] shows the tractability borderline regarding schedulability with dynamic priority schedulers.…”
Section: A Prior Workmentioning
confidence: 99%